A ZnO microcantilever for high-frequency nanopositioning : modeling, fabrication and characterization - Yuan, Yanhui (2013)
Previous studies on zinc oxide (ZnO) microcantilevers have been focused on applications in the atomic force microscopy (AFM). Characteristics of ZnO microcantilever actuators were not thoroughly investigated in those studies. This paper reports modeling, fabrication and characterization of a piezoelectric ZnO microcantilever actuator for high-frequency nanopositioning. Main characteristics of the ZnO microcantilever, i.e. resonant frequency, actuation sensitivity and force-deflection relationship, have been studied by modeling and experiments. Analytic equations of the resonant frequency and actuation sensitivity were derived. Tip deflection as a function of driving voltage and external load was formulated. Effects of major geometric dimensions on the performance of piezoelectric ZnO cantilevers were demonstrated with numerical results. A prototype was designed for applications requiring micro-Newton actuation forces with driving frequencies above 10 kHz. The microfabricated cantilever was characterized for its resonant frequency and actuation sensitivity. Impedance analysis identified the resonant frequency at 53 kHz which was in excellent agreement with the frequency response function. Steady-state actuation sensitivity at 15 kHz was found to be 12 nm/V with a bandwidth of 27 kHz.